Current trends and landscape of drug resistance in renal cell carcinoma: a bibliometric analysis - Kenan Zhang; Shixu Chen; Zhenzhen Zhou; Shuanbao Yu; Yonghao Zhan; Xuepei Zhang (Discover Oncology)
Abstract Introduction Renal cell carcinoma (RCC) is a common type of kidney cancer, and the prognosis for patients with advanced-stage disease remains poor. One major obstacle is the development of drug resistance, which severely limits the effectiveness of therapeutic interventions. This bibliometric study aims to provide a comprehensive overview of current research trends on drug resistance in RCC. Methods This study examines publications on drug resistance in RCC from 2000 to 2023, sourced from the Web of Science Core Collection (WoSCC). Detailed analyses were conducted to identify research hotspots, academic collaborations, and emerging trends. CiteSpace, SCImago Graphica, and VOSviewer were utilized to conduct these analyses comprehensively. Results This study analyzed a total of 2,804 publications from the WoSCC database. The number of annual publications showed a consistent upward trend, with an average annual growth rate of 8.12%. The United States had the highest number of publications, followed by China and Japan. The most productive institutions were the University of Texas System, Harvard University, and the National Institutes of Health (NIH). Alfred H. Schinkel emerged as the most prolific author, also having the highest H-index. The three most frequent research categories were oncology, pharmacology and pharmacy, and biochemistry and molecular biology. The evolution of research topics was assessed in 5-year intervals, revealing that recent themes such as ferroptosis and immunotherapy have gained increasing attention. Keyword analysis indicated a shift in research focus toward cell lipid metabolism, androgen receptor and specific molecular signatures. Conclusion This study offers the first comprehensive bibliometric analysis specifically focused on drug resistance in RCC. It identifies current research trends, highlights emerging hotspots, and provides insights into key contributors and ongoing challenges in the field. Our study provides a theoretical reference and guidance to guide future research efforts to address drug resistance in RCC more effectively.